HIGHLIGHTING ENGLISH EDUCATION IN INDONESIA; FACTS, CONCEPTS, PRINCIPLES AND PROCEDURES - Achmad Komaruddin (English Language Teaching Journal, 2024)
The objectives of this study is to know the explanation about English education in Indonesia in terms of facts, concepts, principles and procedures through library research. The findings show that the education in Indonesia implements the curriculum in which its implementation is based on various aspects need. While in terms of English education, it is done through formal dan non-formal education. Formal education is such as elementary school, junior high school, senior high school and college. While non-formal education is such as courses, private class, etc. Eventually, the problem of English study in Indonesia is the teachers’ innovation in creating English as fun as possible. Keywords: Curriculum, Learning, evaluation